2002
DOI: 10.1212/wnl.59.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the human body

Abstract: The demonstration that body knowledge may be preserved despite substantial semantic deficits involving other types of semantic information argues that body knowledge is a distinct and dissociable semantic category. These data are interpreted as support for a model of semantics that proposes that knowledge is distributed across different cortical regions reflecting the manner in which the information was acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 42 publications
1
79
0
4
Order By: Relevance
“…Other studies have reported selective sparing of lexical-semantic knowledge about bodies (e.g., Coslett et al, 2002;Shelton, Fouch, & Caramazza, 1998), providing clear doubledissociations between knowledge about bodies and other domains. Nevertheless semantic knowledge about the body may be unusually resilient to impairment (e.g., Capitani, Laiacona, Mahon, & Caramazza, 2003;Gainotti, 2004;Kemmerer & Tranel, 2008).…”
Section: Lexical-semantic Knowledge About Bodiesmentioning
confidence: 73%
See 1 more Smart Citation
“…Other studies have reported selective sparing of lexical-semantic knowledge about bodies (e.g., Coslett et al, 2002;Shelton, Fouch, & Caramazza, 1998), providing clear doubledissociations between knowledge about bodies and other domains. Nevertheless semantic knowledge about the body may be unusually resilient to impairment (e.g., Capitani, Laiacona, Mahon, & Caramazza, 2003;Gainotti, 2004;Kemmerer & Tranel, 2008).…”
Section: Lexical-semantic Knowledge About Bodiesmentioning
confidence: 73%
“…Coslett, Saffran, & Schwoebel, 2002). Indeed, several researchers have reported cases of patients with selective impairment (e.g., Dennis, 1976;Goodglass, Klein, Carey, & Jones, 1966;Laiacona, Allamono, Lorenzi, and Capitani, 2006;Suzuki, Yamadori, & Fujii, 1997) of lexicalsemantic knowledge related to the body following brain damage.…”
Section: Lexical-semantic Knowledge About Bodiesmentioning
confidence: 99%
“…Clearly, probing a hypothetical neural differentiation between these components of the action semantic system is beyond the scope of our experiment and deserves further investigations. Likewise, we do not believe that these data are sufficient to ascertain the segregation of a dedicated action-semantic system according to the multiple semantic systems hypothesis, although numerous studies suggest that knowledge from different conceptual categories depends on partially segregated neural systems [e.g., Coslett et al, 2002;Martin et al, 1996;Perani et al, 1999;Silveri et al, 1997;Tranel et al, 1997;Warrington and McCarthy, 1987; for critical discussion see Phillips et al, 2002].…”
Section: Innervatory Patternsmentioning
confidence: 80%
“…Interestingly, such deficits appear to be unrelated to a general deficit in spatial abilities or in semantic naming difficulties, as evidenced by a spared performance when animals or manmade object parts are used instead. Thereby, this patients' behavior stands in contrast with the difficulties experienced by patients with a specific loss of body semantics (Coslett, Saffran, & Schwoebel, 2002;Kemmerer & Tranel, 2008;Laiacona, Allamano, Lorenzi, & Capitani, 2006;Schwoebel, Buxbaum, & Coslett, 2004;Schwoebel & Coslett, 2005;Shelton, Fouch, & Caramazza, 1998;Suzuki, Yamadori, Fuji, & Abe, 1997). These patients are unable to understand the meaning of words referring to body parts and to relate a word referring to a body part to its referent.…”
Section: Introductionmentioning
confidence: 72%
“…Based on these findings it has been suggested that body semantics, i.e. semantic knowledge of the human body, comprises a distinct conceptual category that can be selectively impaired or spared (Coslett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%